A review on synthetic inhibitors of dual-specific tyrosine phosphorylation-regulated kinase 1A (DYRK1A) for the treatment of Alzheimer's disease (AD) - Gehlot P.; Pathak R.; Kumar S.; Choudhary N.K.; Vyas V.K. (My University, 2025)
Alzheimer's disease (AD) is a complex disorder that is influenced by a number of variables, such as age, gender, environmental factors, disease, lifestyle, infections, and many more. The main characteristic of AD is the formation of amyloid plaque and neurofibrillary tangles (NFT), which are caused by various reasons such as inflammation, impairment of neurotransmitters, hyperphosphorylation of tau protein, generation of toxic amyloid beta (Aβ) 40/42, oxidative stress, etc. Protein kinases located in chromosome 21, namely dual-specific tyrosine phosphorylation-regulated kinase 1A (DYRK1A), play an essential role in the pathogenesis of AD. DYRK1A stimulates the Aβ peptide aggregation and phosphorylation of tau protein to generate the NFT formation that causes neurodegeneration. Thus, DYRK1A is associated with AD, and inhibition of DYRK1A has the potential to treat AD. In this review, we discussed the pathophysiology of AD, various factors responsible for AD, and the role of DYRK1A in AD. We have also discussed the latest therapeutic potential of DYRK1A inhibitors for neurogenerative disease, along with their structure–activity relationship (SAR) studies. This article provides valuable information for guiding the future discovery of novel and target-specific DYRK1A inhibitors over other kinases and their structural optimization to treat AD. © 2024 Elsevier Ltd